Seasonal and Temporal Drivers Influencing Phytoplankton Community in Kuwait Marine Waters: Documenting a Changing Landscape in the Gulf - Devlin, Michelle J.; Breckels, Mark; Graves, Carolyn A.; Barry, Jon; Capuzzo, Elisa; Huerta, Francisco P.; Al Ajmi, Fahad; Al-Hussain, Mona M.; LeQuesne, William J. F.; Lyons, Brett P. (Frontiers in Marine Science, 2019)
This assessment of environmental drivers and phytoplankton community in Kuwait (Arabian Gulf) arises from a scenario in which the rapid urbanisation in recent decades has caused significant changes from pre-industrial conditions. To present these changes, we have analysed a long-term water quality dataset (1984 – 2017) and explored potential changes in a sub-set of phytoplankton community data by analyzing ten years of phytoplankton data available (2007 – 2016) for Kuwait Bay and the Northern Gulf waters. The longer-term water quality data shows that dissolved nutrient concentration, with the exception of a recent fall in SiO4, have been increasing over 30 years but with a high degree of variability reflecting the changing rate of inputs from coastal pollution and the Shatt Al-Arab River. The correlative analysis between the environmental parameters and phytoplankton in the period from 2007 to 2016 show the seasonal variability of the phytoplankton are influenced by several factors stressors including higher temperatures, coastal sewage runoff, and changing salinity. Whilst the rapid and extended nutrient enrichment data move Kuwait coastal waters into a eutrophic state, the temporal patterns highlight that recent changes in phytoplankton community are more likely to be responding to cumulative pressures of eutrophication, climate and salinity changes. The seasonal and temporal changes in the coastal phytoplankton community, alongside long term deteriorating water quality present management challenges of managing local and external pressures. Continued declines in water quality within a system that is influenced by a warming climate can potentially have long-term consequences on the resilience of the Northern Gulf environment.